2022
DOI: 10.1080/19490976.2022.2156254
|View full text |Cite
|
Sign up to set email alerts
|

Diet and the gut-lung axis in cystic fibrosis – direct & indirect links

Abstract: Cystic fibrosis (CF) is a multisystem, autosomal, recessive disease primarily affecting the lungs, pancreas, gastrointestinal tract, and liver. Whilst there is increasing evidence of a microbial ‘gut-lung axis’ in chronic respiratory conditions, there has been limited analysis of such a concept in CF. We performed a comprehensive dietary and microbiota analysis to explore the interactions between diet, gastrointestinal microbiota, respiratory microbiota, and clinical outcomes in children with CF. Our results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Correlations were also established between the intake of specific components such as fibres and fatty acids and the intestinal microbiota composition in pwCF. 157 Although the findings of the study should be interpreted with caution given its small sample and crosssectional design; they provide evidence highlighting the importance of the quality of the CF diet for intestinal health.…”
Section: Gastrointestinal Healthmentioning
confidence: 87%
See 2 more Smart Citations
“…Correlations were also established between the intake of specific components such as fibres and fatty acids and the intestinal microbiota composition in pwCF. 157 Although the findings of the study should be interpreted with caution given its small sample and crosssectional design; they provide evidence highlighting the importance of the quality of the CF diet for intestinal health.…”
Section: Gastrointestinal Healthmentioning
confidence: 87%
“…A recent study investigating the dietary intake of young pwCF showed that their relative intake of resistant starch, whole grains and dietary fibres (total, insoluble and soluble) was lower than that of healthy controls. 157 Participants with CF also reported a greater proportion of energy intake derived from non-core foods (e.g., sweetened drinks, packaged snacks) than non-CF participants. Such higher intakes were correlated with faecal calprotectin levels (a marker of intestinal inflammation).…”
Section: Gastrointestinal Healthmentioning
confidence: 92%
See 1 more Smart Citation
“…This encompasses pulmonary antibiotic usage, which was a key explanator across our multivariate analyses and of high prevalence across pwCF undertaking extended ETI. Though not investigated in the current study, additional research into the ability of specific dietary intake and probiotic usage to shape the microbiota and patient outcomes is desirable [6264], especially since resilience of the gut microbiota has been recently suggested following diet and exercise intervention in pwCF [65]. It could be that long-term substantial changes to such factors are necessary for subsequent beneficial changes to the intestinal microbiome in an era of modulator therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence suggesting an altered gut flora in pwCF with more frequent dysbiosis 125 . Many suffer from GI symptoms, 126 and diet is understandably in focus with its links to short‐chain fatty acids (SCFA), inflammation and modulator role in the GI tract 127 …”
Section: Introductionmentioning
confidence: 99%